NGROWOT URGENCY (CASE STUDY OF SANTRI ISLAMIC BUILDING SCHOOL OF JAGAD ‘ALIMUSSIRRY) IN ACHIEVING PEACE OF THE SOUL - Puspita, Nur Layli Indah; Aliyah, Himatul (Journal Intellectual Sufism Research (JISR), 2020)
Abstract. In this life, there are so many difficulties in life that make the heart anxious and make the heart uneasy, therefore it is necessary to get closer to Allah SWT so that the heart becomes calm, one of which is by doing tirakat, one of which is by ngrowot. This study aims to determine how peace the soul of Jagad ‘Alimussirry islamic buildingschool students, to know the effect of tirakat ngrowot in achieving peace of mind, and to find out how important the tirakat ngrowot is carried out by students of Jagad ‘Alimussirry islamic buildingschool in achieving peace of mind. This research is a descriptive qualitative research conducted by means of field observations and interviews with Jagad ‘Alimussirry islamic buildingschool students who do tirakat ngrowot. The results of this study were the students of the Jagad ‘Alimussirry islamic buildingschool Students do tirakat ngrowot sincerely and are happy to carry out the duties of the kyai's brother. Initial conditions or problems experienced by students of the Jagad ‘Alimussirry islamic buildingschool are responsibility issues, campus problems and the cottage environment. One of the impacts that can be seen during or after doing tirakat ngrowot is being a person who is resilient, patient, and can apply the Jagad‘Alimussirry Islamic Building school motto in everyday life. And also getting blessed to leave as it is facilitated in education and looking for work.